LITERATUR REVIEW: RELAXATION HANDHELD FINGER TECHNIQUE TERHADAP PENURUNAN NYERI PADA PASIEN POST SECTIO CAESAREA - Muh Alfajar; Iis Sriningsih; Asri Herawati (Jurnal Ilmu Keperawatan Maternitas, 2022)
Background: Every surgical procedure, including SC surgery, must beaccompanied by pain. SC pain is caused by surgical wounds on the frontwall of the abdomen and uterine wall (Sarwono, 2009). Based on thisphenomenon, pain in post-SC patients needs serious treatment because itcan have an impact both physically and psychologically. Post-SC painmanagement can be done pharmacologically and non-pharmacologically.One of the non-pharmacological studies that are effective for reducingpain in post-SC patients is relaxation handheld finger techniquePurpose: The purpose of writing this scientific paper is to provide an ideaof applying finger grip relaxation therapy to reduce pain intensity so thatit can increase post-SC patient comfort.Method: The method used is a literature review or a review of fiveresearch journals about the effect of finger grip relaxation on post SC pain.The search for these journals was done through PubMed, Onesearch, andGoogle Scholar.Result: Based on a search from five previous research journals, it wasfound that the patient's criteria included being fully aware andcooperative, not experiencing post SC complications, not experiencingother pain, not experiencing mental or mental disorders, and not havingphysical disorders such as muscle stiffness. Giving effective interventionusing a duration of15 minutes, 6-8 hours after administration of analgesics and post SC over12 hours. The steps for giving the intervention include the patient beingadvised to sit or lie down quietly, grasping five fingers, closing the eyes,focusing, and inhaling slowly through the nose, exhaling slowly throughthe mouth.Recommendation: The finger grip relaxation technique can be used as areference in the management literature as a standard operating procedure(SOP) for handling post SC pain reduction.